ANALISIS LAPORAN KEUANGAN DENGAN METODE KOMPARATIF PADA PT. TIMAH,TBK PERIODE TAHUN 2016- 2018 - Elisabet Sury; Erni Setiawati; Devy Putri Milanda (OBOR: Oikonomia Borneo, 2020)
This research is a type of descriptive research, in which this study illustrates and explains several improvements in the comparative method by using financial ratios on PT Timah Tbk using balance sheet reports and income statements from financial statements. The data used in this study are secondary data, obtained from PT Timah Tbk. Comparative methods used are liquidity ratios including current ratio, solvency including debt to total equity ratio, Activities including inventory turnover, Profitability including Retutnt on Investment (ROI)